2023
DOI: 10.31234/osf.io/g84pw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Infants who are rarely spoken to nevertheless understand many words

Abstract: Theories of language development---informed largely by studies of Western, middle-class infants---have highlighted the language that caregivers direct to children as a key driver of language learning. However, some have argued that language development unfolds similarly across environmental contexts, including those in which child-directed language is scarce. This raises the possibility that children adapt their learning strategies to the language available in their environments, such that some children come t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Moreover, emic research can challenge long‐held beliefs about developmental mechanisms and provide evidence for alternative or multiple mechanisms. For example, research conducted with Tseltal families in the south of México demonstrated that infants can acquire language skills through overhearing conversations, challenging the dominant notion of child‐directed speech as a critical driver for language acquisition (Foushee & Srinivasan, 2023). In the same vein, research in collectivistic countries in the Majority World challenges the typical characteristics associated with adolescence in the more individualistic contexts in the Global North (Wang et al., 2020).…”
Section: Contributions Of Majority World Researchmentioning
confidence: 99%
“…Moreover, emic research can challenge long‐held beliefs about developmental mechanisms and provide evidence for alternative or multiple mechanisms. For example, research conducted with Tseltal families in the south of México demonstrated that infants can acquire language skills through overhearing conversations, challenging the dominant notion of child‐directed speech as a critical driver for language acquisition (Foushee & Srinivasan, 2023). In the same vein, research in collectivistic countries in the Majority World challenges the typical characteristics associated with adolescence in the more individualistic contexts in the Global North (Wang et al., 2020).…”
Section: Contributions Of Majority World Researchmentioning
confidence: 99%